Implementasi Algoritma Enkripsi Snow-V pada Wireless Sensor Network (WSN) - Yulius Adi Pratama; Agung Setia Budi; Ari Kusyanti (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
Wireless sensor network (WSN) is a technology consisting of a collection of nodes that are spread out within the scope of the system that can be used for monitoring, tracking and controlling equipment. Each node on the WSN uses a wireless network in exchanging data so that it allows data to be seen and collected by other parties by eavesdropping on the data exchange path between nodes. The data seen and collected by other parties may contain sensitive information such as identity, location, etc. In this study the author uses the streamciper method in securing data with the Snow-v algorithm. Streamciper was chosen because of its simplicity in securing data and its speed. The Snow-v algorithm is a new algorithm that offers speed and lightness in running the algorithm. The Snow-v algorithm is also a proposal in the encryption of perimits in 5G systems. In this study, the snow-v algorithm is used as a keystream generator in the streamciper. In this study, using nRF24L01 as a communication module for data exchange between nodes using radio frequency media and Arduino Uno as a tool used as a medium to run the Streamciper method and the Snow-v algorithm. From the research results, the data cannot be read by other pilaks who are eavesdropping on the exchange of data between nodes. In this study, the average time required for the node to encrypt is 241 ms and the time required to decrypt the data is 185 ms.